2022
DOI: 10.1016/j.ijnurstu.2021.104142
|View full text |Cite
|
Sign up to set email alerts
|

Profiling vaccine believers and skeptics in nurses: A latent profile analysis

Abstract: Background A tailored immunization program is deemed more successful in encouraging vaccination. Understanding the profiles of vaccine hesitancy constructs in nurses can help policymakers in devising such programs. Encouraging vaccination in nurses is an important step in building public confidence in the upcoming COVID-19 and influenza vaccination campaigns. Objectives Using a person-centered approach, this study aimed to reveal the profiles of the 5C psychological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 74 publications
(96 reference statements)
8
36
1
Order By: Relevance
“…In this study, nurses had higher median score in confidence (Median = 6.33), calculation (Median = 6.00), and collective responsibility (Median = 6.50) and lower median score in complacency (Median = 2.67) and constraints (M = 1.25). The overall distribution of the five dimensions is similar to prior research on nurses in Hong Kong ( 30 ). However, our findings contradict Betsch's ( 31 ) assumptions about the structure of the calculation.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In this study, nurses had higher median score in confidence (Median = 6.33), calculation (Median = 6.00), and collective responsibility (Median = 6.50) and lower median score in complacency (Median = 2.67) and constraints (M = 1.25). The overall distribution of the five dimensions is similar to prior research on nurses in Hong Kong ( 30 ). However, our findings contradict Betsch's ( 31 ) assumptions about the structure of the calculation.…”
Section: Discussionsupporting
confidence: 76%
“…As expected, all 5C indicators were correlated with each other and all were significantly associated with COVID-19 vaccine intention. However, a positive correlation was calculated with vaccination intention ( r = 0.118, p < 0.01), contradicting the original authors' hypothesis ( 31 ) but matching a study in the Hong Kong nurse population ( 30 ). In addition, the same pattern was detected for the frequency of paying attention to COVID-19 vaccine news.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Our current four profile pattern in the full sample was very similar to the one found in a survey conducted among nurses during the early epidemic phase in March 2020 except that the "contradictor" profile was missing (18). The "middler" and "outsider" profiles defined in our previous work were classified as fence-sitters and apathetics, respectively in this study.…”
Section: Principal Findingssupporting
confidence: 84%
“…For example, five profiles have been identified among Hong Kong health workers. The analysis revealed that the profile with the highest intention to vaccinate was characterized by lower educational attainment, more long-term illness, higher work stress, and greater trust in the government, among other factors [ 26 ]. In another study, motivation to vaccinate against both COVID-19 and seasonal influenza was examined in Taiwan [ 27 ].…”
Section: Introductionmentioning
confidence: 99%